Ophthalmoplegia Due to Miller Fisher Syndrome in a Patient With Myasthenia Gravis - Brusa, Roberta; Faravelli, Irene; Gagliardi, Delia; Magri, Francesca; Cogiamanian, Filippo; Saccomanno, Domenica; Cinnante, Claudia; Mauri, Eleonora; Abati, Elena; Bresolin, Nereo; Corti, Stefania; Comi, Giacomo Pietro (Frontiers in Neurology, 2019)
Here we describe a 79 years old man admitted to our unit for worsening diplopia and fatigue, started a few weeks after an episode of bronchitis and flu vaccination. Past medical history included myasthenia gravis well controlled by Pyridostigmine, Azathioprine and Prednisone. During the first days, the patient developed progressive ocular movement abnormalities up to complete external ophthalmoplegia, severe limb and gait ataxia and mild dysarthria. Deep tendon reflexes were absent in lower limbs. Since not all the symptoms were explainable with the previous diagnosis of myasthenia gravis, other etiologies were investigated. Brain MRI and cerebrospinal fluid analysis were normal. Electromyography showed a pattern of predominantly sensory multiple radiculoneuritis. Suspecting Miller-Fisher syndrome, the patient was treated with plasmapheresis with subsequent clinical improvement. Antibodies against GQ1b turned out to be positive. Miller Fisher Syndrome is an immune-mediated neuropathy presenting with ophthalmoplegia, ataxia and areflexia. Even if only a few cases of MFS overlapping with MG have been described so far, the coexistence of two different autoimmune disorders can occur. It is always important to evaluate possible differential diagnosis even in case of known compatible diseases, especially when some clinical features seem atypical.